2012
DOI: 10.4081/rt.2012.e46
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Temporal Arteritis Associated with Overlying Basal Cell Carcinoma: Co-Incidence or Connection?

Abstract: Giant cell arteritis is a granulomatous vasculitis of large and medium sized arteries manifesting as temporal arteritis and/or polymyalgia rheumatica. The histological assessment of temporal artery biopsies is frequently encountered in anatomical pathology and has important diagnostic consequences in patients clinically suspected of having giant cell arteritis. We present an intriguing case of giant cell arteritis associated with a Basal cell carcinoma and discuss the ongoing controversy pertaining to the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[60][61][62][63] However, some cases of concomitant nonmelanoma skin cancer and GCA have been reported. 64,65 Mahe et al 65 reported a patient referred to the dermatology clinic due to a left temporal ulcerating skin lesion. Excision of the cutaneous lesion revealed an ulcerating basal cell carcinoma.…”
Section: Cutaneous Diseases Associated With Giant Cell Arteritis Genementioning
confidence: 99%
“…[60][61][62][63] However, some cases of concomitant nonmelanoma skin cancer and GCA have been reported. 64,65 Mahe et al 65 reported a patient referred to the dermatology clinic due to a left temporal ulcerating skin lesion. Excision of the cutaneous lesion revealed an ulcerating basal cell carcinoma.…”
Section: Cutaneous Diseases Associated With Giant Cell Arteritis Genementioning
confidence: 99%